FRI0292 TREATMENT RESPONSE TO BIOLOGICAL DISEASE-MODIFYING ANTI-RHEUMATIC DRUGS IS ASSOCIATED WITH FAVORABLE CHANGES OF THE BODY COMPOSITION IN PATIENTS WITH ANKYLOSING SPONDYLITIS. (2nd June 2020) - Rios Rodriguez, V.; Protopopov, M.; Proft, F.; Rademacher, J.; Muche, B.; Weber, A. K.; Lüders, S.; Haibel, H.; Verba, M.; Sieper, J.; Poddubnyy, D.
Abstract : Background: There is few data available regarding differences in body composition and its possible changes in patients with ankylosing spondylitis (AS) treated with biological disease-modifying anti-rheumatic drugs (bDMARDs). An increase of body weight and lean mass in patients receiving TNF inhibitors, as well as a possible muscle wasting by high disease activity have been previously described. Bioelectrical impedance analysis (BIA) is a valid method to assess body composition and allows to distinguish between fat, fat-free mass and skeletal muscle mass. Objectives: To evaluate changes in body composition in patients with AS after 6 months of treatment with bDMARDs. Methods: Patients with a diagnosis of AS, fulfilling the modified New York criteria and starting a bDMARD therapy were included in the extension of the prospective German Spondyloarthritis Inception Cohort (GESPIC). All patients had high disease activity (BASDAI >=4 and/or ASDAS >=2.1) despite previous treatment with nonsteroidal anti-inflammatory drugs. Disease activity and body composition were assessed at baseline and after 6 months of bDMARD treatment. Body composition was assessed by the BIA with the seca© mBCA 515 device (SECA Deutschland GmbH, Hamburg/Germany) and included the following parameters: weight, body mass index (BMI), fat mass index (FMI), fat free mass index (FFMI), skeletal muscle mass value (SMM), and visceral adipose tissue value (VAT). Response to a bDMARD therapy was defined as achievement of clinically important improvement of ASDAS (>=1.1). Results: A total of 129 patients (66.7% male) with AS were recruited in this cohort extension between 2015 and 2019. The mean (mean ± SD) age was 36.2 ± 10.3 years, and symptom duration was 10.7 ± 9.1 years. HLA-B27 test was positive in 89.1% patients. BIA was assessed in 77 patients; the baseline characteristics of these patients were similar to those of the whole cohort. Of these, 75 patients were treated with TNF inhibitors and 2 patients were treated with an IL-17A inhibitor. After 6 months of a bDMARD treatment, body composition changed significantly with an increase of weight and BMI due to the gain of FMI but also of FFMI and SMM, while there was no increase of the visceral fat – table. In responders (improvement of ASDAS>=1.1 after 6 months) the results were similar to the whole group with a significantly gain (mean±SD) on BMI, FMI, FFMI and SMM (0.3 ± 1.4 kg/m 2, 0.3 ± 1.0 kg/m 2, 0.2 ±0.5 kg/m 2, 0.5 ± 1.2 kg, p<0.05, respectively). In non-responders, there were no significant changes on the body composition after 6 months of treatment. Conclusion: Treatment with bDMARDs is associated with favorable changes of the body composition with increase of the muscle mass but not of the visceral fat. These changes were evident in treatment responders only. Acknowledgments: GESPIC has been financially suported by ArthroMark and METARTHROS projects Disclosure of Interests: Valeria Rios Rodriguez Consultant of: Abbvie, Novartis, Mikhail Protopopov Consultant of: Novartis, Fabian Proft Grant/research support from: Novartis Pharma GmbH, Consultant of: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: Consultancy / speaker fees from: Abbvie, BMS, Celgene, Lilly, MSD, Novartis, Pfizer, Roche, UCB, Judith Rademacher: None declared, Burkhard Muche: None declared, Anne Katrin Weber: None declared, Susanne Lüders: None declared, Hildrun Haibel Consultant of: Abbvie, Jansen, MSD, and Novartis, Speakers bureau: Abbvie, Jansen, MSD, and Novartis, Maryna Verba: None declared, Joachim Sieper Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Speakers bureau: AbbVie, Boehringer Ingelheim, Eli Lilly and Company, Janssen, Merck, Novartis, Pfizer, Roche, and UCB Pharma, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB